ANALISIS BEBAN PAJAK TANGGUHAN DAN BEBAN PAJAK KINI UNTUK MENDETEKSI MANAJEMEN LABA - Elisa Yuliana, 08.05.52.0144; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2012)
This research is a testing that examined the effect and analyze the changes in deferred tax expense and current tax expense on earnings management to avoid earnings decreases in manufacturing companies that go public in Indonesia.The population in this study is a company engaged in the manufacturing sector are listed in Indonesia Stock Exchange (BEI) in 2008-2010. Sampling technique using a purposive sampling. According to established criteria contained 32 samples. Analysis technique used is logistic regression.The results showed that the change in deferred tax expense have a significant effect can be used to detect earnings management to avoid earnings decreases. Meanwhile, the current income tax can not be used for detecting earnings management to avoid earnings decreases.Keywords: Earnings Management, Accrual, Cash Flow Operating, Deferred Tax Expense, Deferred Tax Liabilities, Deferred Tax Assets, Current tax expense